2017
DOI: 10.1016/j.aju.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide and decision-making protocol for the management of complex renal cystic masses

Abstract: ObjectivesTo analyse the management, pathology and outcomes of complex renal cystic masses (CRCM) and to develop a decision-making tool for daily clinical care using the Bosniak classification system for CRCM.Patients and methodsA comprehensive dataset of 185 patients with 188 CRCM and a minimum follow-up of 3 years were analysed for management, pathology and outcomes.ResultsWe analysed 35 Bosniak II, 34 Bosniak IIF, 58 Bosniak III, and 61 Bosniak IV lesions. The overall incidence of renal cell carcinoma was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Intravenous urography is an effective imaging method for diagnosis of medullary sponge kidney and ADPKD, which seen with thin prolonged calyces described as a spider-leg deformity; it determines the obstruction level and renal excretion (11,17,27) . CT scan is very sensitive imaging study for the diagnosis and characterizing of simple renal cysts and complex cystic mass with solid components or thick septae with enhancement suspected of renal cell carcinoma, detection of complications and associated abnormalities consistent with reported by Weibi et al in 2017 (28) . Non-contrasted CT urography and US images detects non-radiopaque stones and used in renal failure (29) .…”
Section: Figure 1 Ivu Shows Right Renal Agenesis and Double Left Pelv...supporting
confidence: 79%
“…Intravenous urography is an effective imaging method for diagnosis of medullary sponge kidney and ADPKD, which seen with thin prolonged calyces described as a spider-leg deformity; it determines the obstruction level and renal excretion (11,17,27) . CT scan is very sensitive imaging study for the diagnosis and characterizing of simple renal cysts and complex cystic mass with solid components or thick septae with enhancement suspected of renal cell carcinoma, detection of complications and associated abnormalities consistent with reported by Weibi et al in 2017 (28) . Non-contrasted CT urography and US images detects non-radiopaque stones and used in renal failure (29) .…”
Section: Figure 1 Ivu Shows Right Renal Agenesis and Double Left Pelv...supporting
confidence: 79%
“…Typically, the size of tubulocystic RCCs (TCRCC) is small, and approximately 40.0% of them are smaller than 2 cm [ 18 ], unlike the FH-deficient RCC observed in our cases. As reported in the literature, cystic pattern and rim-like or egg-shell calcification are common in Xp11.2/TFE RCC [ 25 26 27 ]. However, the probability of a polycystic shape was higher, and typical calcification was relatively rare in FH-deficient RCC.…”
Section: Discussionmentioning
confidence: 95%
“…Grade IIF is between grades II and III. There are more lesions in grade IIF in clinic, so the diagnosis is relatively difficult (18). Studies have shown that ultrasound combined with Bosniak criteria can improve the diagnostic rate of benign and malignant renal cystic lesions (19).…”
Section: Discussionmentioning
confidence: 99%